Manfaat Perawatan Kaki pada Pasien Diabetes Melitus untuk Optimalisasi Perfusi Perifer Ektremitas Bawah - Widyaastuti, Eny Erlinda; Siburian, Christine Handayani; Yasin, Dudella Desnani Firman (The Indonesian Institute of Science and Technology Research, 2025)
Diabetes mellitus causes microvascular and macrovascular changes as a result of metabolic syndrome. Long-term microvascular changes will lead to the emergence of neuropathy that leads to diabetic ulcers. Therefore, in an effort to promote and prevent complications of diabetes mellitus, foot care (foot spa) is carried out by paying attention to hygiene, foot moisture, peripheral circulatory function of the feet and motor function. This study was conducted with a case study approach involving 10 people with diabetes mellitus and did foot spa for 2 consecutive months. Implementation of foot care (foot spa) was carried out at home accompanied by cadres in monitoring. The purpose of this study was to obtain an overview of the application of foot spa in optimizing peripheral perfusion function and preventing further complications of diabetic ulcers. Results: there was an increase in foot moisture, pulse quality and CRT, ABI values ​​and this was obtained by alignment of normoglycemia and blood pressure values.